Improvement of individual learning with mentoring programs for first-year undergraduate students - Queiruga-Dios, Marián; Perez-Araujo, Alvaro; de Ávila-Arias, Carmen Romero; Queiruga-Dios, Araceli (Frontiers in Psychology, 2023)
Introduction This study presents a brief analysis of Spanish universities that promote mentoring programs with students. These mentoring programs are divided into different categories depending on the persons (faculty or students) involved in the process and their characteristics (for novice, senior, or international students). The case of the Universidad Francisco de Vitoria is presented, where first-year students from all undergraduate degrees are involved in an annual course where the core part is related to formal mentoring activities. Methods This study analyzes undergraduate degree students' outcomes and results from 10 different degrees for a period of 4 academic years (from 2016–2017 to 2019–2020). This first analysis corresponds to students' activities and marks awarded on the assessment of the assigned mentoring tasks related to the competencies of critical thinking, proactivity, personal knowledge (with the objective of acceptance and improvement), and the ability to ask transcendental questions. Then, a reliable and valid survey, conducted every year to all senior students, was used to get feedback from students. Results After a quantitative and qualitative analysis of students' results, it was noticed that they become more confident in their studies when they engage in mentoring-based courses and sessions, and this benefits their lives. All this information led to the improvement of the mentoring process.